Outcome of the treatment of developmental dysplasia of the hip after walking age with open reduction, varus derotation osteotomy with femoral shortening and acetabular osteotomy - Mahmud, Al-Imran; Noman, Saifullah Al; Minto, M. C. Paul (International Journal of Research in Orthopaedics, 2025)
Background: The principles of treatment of developmental dysplasia of hip after walking age are different than those of infants and neonates. The purpose of this study is to evaluate the radiographic and functional results of open reduction, varus derotation osteotomy with femoral and acetabular osteotomy of DDH in older children. Methods: Between March 2021 and August 2023, 22 patients underwent one-stage triple procedure of open reduction, varus derotation osteotomy with femoral shortening and acetabular osteotomy for the treatment of DDH. Clinical outcomes were assessed using the modified McKay’s criteria. Radiographic assessment was made using Severin’s scoring system. Results: The mean age at the time of operation was 5.068±1.8535 years (range 3–8 years) with male to female ratio 1:2.66. Mean preoperative acetabular index of the study population was 48.55±7.63 which significantly reduced to 23.68±2.93 postoperatively (p<0.05). The McKay’s score was excellent in 14 (63.6%) hips, good in 02 (9.1%) hips, fair in 01(4.5%) and poor in 05(22.7%) hips. The modified Severin’s class excellent was in 14 (63.6%) hips, good was in 02(9.1%) hips, fair is in 01 (4.5%) hip and poor was in 05 (22.7%) hips at the time of final evaluation as compared to none at the time of presentation. Conclusions: Young children having DDH can be safely treated with an extensive one-stage procedure of open reduction, varus derotation osteotomy with femoral shortening and acetabular osteotomy, without increasing the risk of AVN. This one-stage surgical procedure for managing DDH patients after walking age also revealed acceptable clinical and radiological outcome.